2016
DOI: 10.1038/ncomms13546
|View full text |Cite
|
Sign up to set email alerts
|

PPFIA1 drives active α5β1 integrin recycling and controls fibronectin fibrillogenesis and vascular morphogenesis

Abstract: Basolateral polymerization of cellular fibronectin (FN) into a meshwork drives endothelial cell (EC) polarity and vascular remodelling. However, mechanisms coordinating α5β1 integrin-mediated extracellular FN endocytosis and exocytosis of newly synthesized FN remain elusive. Here we show that, on Rab21-elicited internalization, FN-bound/active α5β1 is recycled to the EC surface. We identify a pathway, comprising the regulators of post-Golgi carrier formation PI4KB and AP-1A, the small GTPase Rab11B, the surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
117
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(130 citation statements)
references
References 63 publications
12
117
1
Order By: Relevance
“…Furthermore, it was recently reported that kank proteins (in cooperation with liprin‐β) control FA dynamics by acting as talin activators that decrease the grip between the integrin–talin complex and actomyosin (Sun et al., ). The notion that liprin‐α1 is relevant for FA‐proximal insulin granule localisation (Gan et al., ) is corroborated by the targeting of TGN‐derived secretory vesicles and the polarised secretion of fibronectin from the TGN of vascular endothelial cells (Stehbens et al., ; Mana et al., ). Unfortunately, not much is known about the specific role of liprin's in β‐cells; however, studies in neuronal and non‐neuronal cells demonstrated that these proteins have several functions related to cell adhesion and spreading, signal transduction and organisation of the cytoskeleton (Asperti et al., ; de Curtis, ).…”
Section: Ecm and Isletsmentioning
confidence: 96%
“…Furthermore, it was recently reported that kank proteins (in cooperation with liprin‐β) control FA dynamics by acting as talin activators that decrease the grip between the integrin–talin complex and actomyosin (Sun et al., ). The notion that liprin‐α1 is relevant for FA‐proximal insulin granule localisation (Gan et al., ) is corroborated by the targeting of TGN‐derived secretory vesicles and the polarised secretion of fibronectin from the TGN of vascular endothelial cells (Stehbens et al., ; Mana et al., ). Unfortunately, not much is known about the specific role of liprin's in β‐cells; however, studies in neuronal and non‐neuronal cells demonstrated that these proteins have several functions related to cell adhesion and spreading, signal transduction and organisation of the cytoskeleton (Asperti et al., ; de Curtis, ).…”
Section: Ecm and Isletsmentioning
confidence: 96%
“…To maintain homeostasis, components of the ECM are continuously turned over and remodeled through several mechanisms, including MMP/matrix metalloproteinase-dependent cleavage, integrin-mediated endocytosis, and lysosomal degradation [39,43,47,134]. Interestingly, RAB11B-mediated integrin ITGA5-ITGB1 internalization and recycling not only degrades FN1, but can also promote fibrillogenesis by facilitating FN1 secretion and vascular morphogenesis [135]. Thus, FN1 matrix assembly is a cell-dependent process that is regulated by secretory and integrin recycling pathways, as well as by integrin surface expression.…”
Section: Reciprocal Regulation Between Autophagy and The Ecmmentioning
confidence: 99%
“…Endocytic recycling also plays a key role in endothelial cell function (particularly through the recycling of integrin cargoes), and VEGFR2 trafficking is important in regulating angiogenic signalling . During angiogenesis, sprouting endothelial cells are classified as either migratory tip cells or proliferative stalk cells, which respond differently to VEGF (vascular endothelial growth factor).…”
Section: Rtk Trafficking and Signalling In Cell Migrationmentioning
confidence: 99%